Martius’ flap for recurrent perineal and rectovaginal fistulae in a patient with Crohn’s disease, endometriosis and a mullerian anomaly - Gaetano Gallo; Alberto Realis Luc; Giuseppe Clerico; Mario Trompetto (BMC Surgery, 2017)
Abstract Background Rectovaginal fistulas represent 5% of all anorectal fistulae and are a disastrous manifestation of Crohn’s disease that negatively affects patients’ social and sexual quality of life. Treatment remains challenging for colorectal surgeons, and the recurrence rate remains high despite the numerous available options. Case presentation We describe a 31-year-old female patient with a Crohn’s disease-related recurrent perineo-vaginal and recto-vaginal fistulae and a concomitant mullerian anomaly. She complained of severe dyspareunia associated with penetration difficulties. The patient’s medical history was also significant for a previous abdominal laparoscopic surgery for endometriosis for the removal of macroscopic nodules and a septate uterus with cervical duplication and a longitudinal vaginal septum. The patient was successfully treated using a Martius’ flap. The postoperative outcome was uneventful, and no recurrence of the fistula occurred at the last follow-up, eight months from the closure of the ileostomy. Conclusion Martius’ flap was first described in 1928, and it is considered a good option in cases of rectovaginal fistulas in patients with Crohn’s disease. The patient should be referred to a colorectal centre with expertise in this disease to increase the surgical success rate.